High-pressure, low-temperature optical and X-ray diffraction studies of semiconducting and incommensurate materials - Burris, Jennifer L., author; Hochhiemer, Hans D., advisor (Colorado State University. Libraries, 2003)
In order to investigate the effects of both high-pressure and low-temperature on materials, a new diamond anvil cell and gasket system has been developed which has increased stability over the previous design. In addition, a system has been designed to perform optical absorption measurements at high-pressure and low-temperature in a diamond anvil cell. Successful high-pressure, low-temperature Raman measurements have been performed on both Cs2MoS4 and KTbP2Se6 using the newly designed cell. Two pressure induced phase transitions have been observed at 77 K in Cs2MoS4 and a single pressure induced phase transition has been observed at 77 K in KTbP2Se6. High pressure, energy dispersive X-ray diffraction measurements of (NH4)2 ZnCl4 have also been performed at constant temperatures up to 150°C. Values of the calculated adiabatic bulk modulus and experimentally determined isothermal bulk modulus for (NH4)2 ZnCl4 and other materials in the A2BX4 have been compiled and discussed.
Keywords: condensation; optics; condensed matter physics